What do sheep do? (Kent, UK : Ticktock Entertainment, 2008)
A simple board book describing the different things sheep like to do.
Cover title.
On board pages.
1.2
K-3
Keywords: Sheep -- Juvenile fiction; Sheep -- Fiction; Sheep -- Fiction